Integrality Attribute of Primary Health Care for children under two years of age in Porto Velho - Rondônia (Research, Society and Development, 2023)
Introduction: Primary Health Care (PHC) presents itself as the user's gateway to the health system, it constitutes a set of care recommendations to solve various health problems. In PHC, health care for children under two years of age is of great importance due to the vulnerability they present during this phase of life. Thus, the importance of assessing the attributes of PHC in relation to the child's health from the perspective of family members/caregivers is highlighted. Objective: To evaluate the presence and extent of the integrality attribute of primary health care for children under two years of age in the city of Porto Velho-RO. Methodology: This is a cross-sectional, evaluative study with a quantitative approach, carried out in family health units in the city of Porto Velho - RO. The sample consisted of 104 family caregivers of children under two years of age. Data collection was carried out from January to February 2020 through the application of the PCATool instrument - child version. Results: The profile of the main family member/caregiver is women (95.1%), who live in a stable relationship (76.9%), have completed high school (37.5%), do not work (75.7% ) and have a per capita income of less than 0.49 (63.7%). The comprehensiveness attribute has an average score of (5.41) for the available services component and (6.61) for the services provided. Conclusion: The attribute evaluated as unsatisfactory by the caregivers, alerts to the need to improve the services offered in the PHC, from the organization and strengthening of the care network aimed at children to the qualification of the professional.